Crosslink between Temozolomide and PD-L1 immune-checkpoint inhibition in glioblastoma multiforme - Heynckes, Sabrina; Daka, Karam; Franco, Pamela; Gaebelein, Annette; Frenking, Jan Hendrik; Doria-Medina, Roberto; Mader, Irina; Delev, Daniel; Schnell, Oliver; Heiland, Dieter Henrik (BMC Cancer, 2019)
Background: In recent years, PD-1/PD-L1 immune checkpoint inhibitors have improved cancer therapy in many tumor types, but no benefit of immune checkpoint therapy has been found in glioblastoma multiforme (GBM). Based on the results of our earlier work, which showed a reduction of PD-L1 expression in patients treated with temozolomide (TMZ), we aimed to investigate the link between TMZ therapy and the immune control point target PD-L1. Methods: RNA-sequencing data from de-novo and recurrent glioblastoma were analyzed by AutoPipe algorithm. Results were confirmed either in a cell model by two primary and one established GBM cell line and specimens of de-novo and recurrent GBM. PD-L1 and pathway activation of the JAK/STAT pathway was analyzed by quantitative real-time PCR and western blot. Results: We found a significant downregulation of the JAK/STAT pathway and immune response in recurrent tumors. The cell model showed an upregulation of PD-L1 after IFNγ treatment, while additional TMZ treatment lead to a reduction of PD-L1 expression and JAK/STAT pathway activation. These findings were confirmed in specimens of de-novo and recurrent glioblastoma. Conclusions: Our results suggest that TMZ therapy leads to a down-regulation of PD-L1 in primary GBM cells. These results support the clinical findings where PD-L1 is significantly reduced in recurrent GBMs. If the target is diminished, it may also lead to impaired efficacy of PD-1/PD-L1 inhibitors such as nivolumab.
CRIS-Team Scopus Importer:2023-09-13
Keywords: PD-L1 immunotherapy; Recurrent GBM; Temozolomide